Analysis of Human Error Potential as a Cause of Work Accident using Sherpa and Heart Method in The Cement Industry - Maulidya, Annisa; Oginawati, Katharina; Suharyanto, Suharyanto (Riviera Publishing, 2023)
This study was conducted to analyze the potential for human error that can cause workplace accidents in the cement industry of PT.X. The study was conducted by conducting observations, interviews, and distributing questionnaires in the mining area and production area. Questionnaires were distributed to 96 people who were mining heavy equipment operators and production operators. The research method used through Human Reliability Analysis with the Hierarchial Task Analysis (HTA) method, knowing the types of errors that occur using the SHERPA method, then calculating the probability of human errors that occur with the HEART method. Based on the results of research using the SHERPA method, the most common types of errors in mining areas and production areas are action errors (60,25%). The type of error that occurs is due to negligence in using personal protective equipment and the work process is not completed properly. Based on research using the HEART method, the greatest opportunity for human error in the mining department is cleaning with dozer with a value of 1,056 and in the production department is in the area of cleaning work with a value of 1,89. Based on the error producing conditions questionnaire (EPCs) for workers in the mining department the most common cause of error is poor equipment / instruments while for workers in the production department is a mismatch between the imagined risk and the actual risk. The recommendations given to companies are to improve work equipment, improve visual displays and provide an appropriate assessment checklist.